Preparing and Publishing a Scientific Manuscript - Padma R Jirge (Wolters Kluwer Medknow Publications, 2017)
Publishing original research in a peer-reviewed and indexed journal is an important milestone for a scientist or a clinician. It is an important parameter to assess academic achievements. However, technical and language barriers may prevent many enthusiasts from ever publishing. This review highlights the important preparatory steps for creating a good manuscript and the most widely used IMRaD (Introduction, Materials and Methods, Results, and Discussion) method for writing a good manuscript. It also provides a brief overview of the submission and review process of a manuscript for publishing in a biomedical journal.